Exploring the Efficacy of Creative Ice Breaking Techniques in Classroom Learning - Sumindar, Chani Ratna; Setiawan, Deni (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
Saturation in the teaching and learning process is something that often happens to students. This can certainly affect the learning process which causes the learning environment to be less conducivef. Therefore , to overcome this, teachers need to apply fun learning methods, one of which is ice breaking. The purpose of this study is to analyze the forms of the application of ice breaking, the impact of the application of ice breaking, and the importance of the application of ice breaking in the learning process. This research uses a qualitative approach. Data was collected by observation, interview, and documentation techniques. Data analysis was performed using Miles and Huberman models and triangulated data validity tests. The results of this study show that classes that apply ice breaking learning are more fun and quality, the application of ice breaking in learning is carried out at the beginning of activities, core activities and final learning activities. The types of ice breaking used in learning are yelling, patting, games, songs, and gestures. Ice Breaking in learning has a positive effect on the classroom atmosphere, the ability of students, and the attitude of students toencourage student enthusiasm and enthusiasm, active learning atmosphere, create a positive environment for students, and build interaction its good in class. Ice breaking is important to be applied in the classroom as an effort to overcome various problems in the learning process related to student saturation, learning motivation, and learning methods.